Incidental Gallbladder Carcinoma Diagnosed After Laparoscopic Cholecystectomy - UPRAK, TEVFİK KIVILCIM (My University, 2022)
Introduction: Laparoscopic cholecystectomy (LC) is one of the most performed general surgeries. Incidental gallbladder carcinoma (IGBC) is diagnosed in 0.3–2.9% of all cholecystectomies and accounts for most detected gallbladder cancers (GBCs). This study aims to evaluate the incidence, clinical, and prognostic features of IGBC diagnosed after LC for benign gallbladder disease. Materials and Methods: We performed a retrospective analysis of patients who underwent cholecystectomy between January 2016 and October 2021 at the Istanbul Sultanbeyli State Hospital General Surgery Clinic. Data regarding the demographics, pathological features of the tumors, and survival times of patients were examined. Results: A total of 745 patients were analyzed. The patients’ median age was 43 (18–78), and the male-tofemale ratio was 137:608. Four patients were diagnosed with gallbladder carcinoma after LC; however, one patient had pre-operative suspicious GBC. Three patients were diagnosed with IGBC. The cancer stages and survival times of the IGBC patients were pT2, pT2, and pT1a and 8, 34, and 40 months, respectively. Conclusion: Most GBCs are detected incidentally. The most significant factor determining the prognosis is an early stage detection. To detect IGBC, cholecystectomy specimens must be carefully examined histopathologically
Keywords: Cancer of gallbladder; Cholelithiasis; Gallbladder neoplasm; Laparoscopic cholecystectomy; Incidental gallbladder carcinoma